Trypan Blue Exclusion Assay Verifies in Vitro Cytotoxicity of New Cis-Platinum (II) Complex in Human Cells (Baghdad Science Journal, 2019)
Various assays are used to determine the toxic effects of drugs at cellular levels in vitro. One of these methods is the dye exclusion assay, which measures membrane integrity in the presence of Trypan blue. Trypan blue the dye which was used in this study to investigate cytotoxic effect of a new Cis –dichloroplatinum (II) complex [(Qu)2PtCl2] on the viability of polymorphonuclear cells (PMNs). Three concentrations of platinum complex were prepared (70, 35and 17.5 µg/ ml) and the results revealed that the percentage of cell viability decreased as the platinum complex concentration increased in comparison with control. The platinum complex exhibited low cytotoxic effects towards healthy cells at the concentrations of 17.5 µg/ ml and 35 µg/ ml, in which the percentage of cell viability was (77.01 ± 6.3) and (72.3± 0.50)respectively, with no significant differences as compared with the control(90.66 ±0.577). The viability was significantly decreased (67.59 ± 3.16) when the cells were treated with the concentration of 70 µg/ ml in comparison with control. These results indicated that the percentage of living cells decreased when treated with high concentrations of [(Qu)2PtCl2], which causes cells death, while low concentrations of the compound show low toxicity. This data indicates that this compound, at these concentrations may be suitable for use as a cancer treatment because it has low toxic effects on the healthy cells.